Serum uric acid as a marker of disease risk, severity, and survival in systemic sclerosis-related pulmonary arterial hypertension. (July 2019) - Simpson, Catherine E.; Damico, Rachel L.; Hummers, Laura; Khair, Rubina M.; Kolb, Todd M.; Hassoun, Paul M.; Mathai, Stephen C.
The object of this paper is to assess associations between serum uric acid (UA) and pulmonary arterial hypertension (PAH) risk, disease severity, and mortality in a well-characterized cohort of systemic sclerosis (SSc) patients referred for evaluation of possible PAH. Consecutive SSc patients aged >18 years with serum UA drawn within two weeks of a diagnostic right heart catheterization (RHC) were included. Associations between baseline serum UA and PAH at RHC were examined using logistic regression and receiver operating characteristic curves. Relationships between UA levels and metrics of disease severity were assessed using Pearson and Spearman correlation. Associations between UA and survival were assessed using Kaplan–Meier analysis and Cox proportional hazard modeling. A total of 162 SSc patients were included; 82 received a diagnosis of PAH at RHC. Patients found to have PAH had significantly higher UA than those without PAH. Elevated baseline UA was associated with significantly increased odds of PAH diagnosis at RHC (odds ratio [OR] = 4.07, 95% confidence interval [CI] = 2.11–7.87, P  < 0.001). Each mg/dL higher UA was associated with a 14% increase in mortality (hazard ratio [HR] = 1.14, 95% CI = 1.02–1.28, P  < 0.05). In multivariable models adjusting for potential confounders of the relationship between UA and survival, UA > 6.3 mg/dL remained significantly associated with increased mortality (HR = 1.84, 95% CI = 1.02–3.32, P  < 0.05). Among SSc patients with suspected PAH, elevated serum UA is associated with increased risk of SSc-PAH. Among individuals diagnosed with SSc-PAH by RHC, UA is associated with disease severity and survival. These results indicate UA is a useful predictor of PAH risk and prognosis in SSc.